Phylogenetic and morphological circumscription of the Orbilia aurantiorubra group - Quijada, Luis; Baral, Hans-Otto; Jaen-Molina, Ruth; Weiss, Michael; Caujapé-Castells, Juli; Beltrán-Tejera, Esperanza (Phytotaxa, 2014)
The phylogeny of Orbilia aurantiorugra and related species is inferred from ITS sequence data. Orbilia aurantiorubra is redefined according to vital taxonomy. Integrated analyses of molecular and morphological data, and ecological (e.g. substrate) and geographical origin suggest the existence of three new species, which are described in this paper: Orbilia xanthoguttulata from Europe, O. succulenticola from the Canary Islands, and O. jugulospora from Ethiopia (Africa) and Taiwan (Southeast Asia).